2014
DOI: 10.1039/c4tc00542b
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-free blue-green emitters for light-emitting electrochemical cells

Abstract: New fluorine-free iridium complexes were synthesized in the aim of improving the performance of blue-green emitting LEECs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 67 publications
0
41
0
Order By: Relevance
“…1,5,19,20 However, high-energy emission is generally desired for many applications. [9][10][11] The former can be realized by including electron-withdrawing groups, such as F, to the phenyl ring of ppy, [21][22][23][24] or using non-conjugated NΛN ligands with strong ligand-field strength; 22, 25-28 the latter can be accomplished through attaching electron-donating groups to bpy, 29 or using electron-rich NΛN ligands, 30,31 such as 2-(1H-pyrazol-1-yl)pyridine (pzpy). [9][10][11] The former can be realized by including electron-withdrawing groups, such as F, to the phenyl ring of ppy, [21][22][23][24] or using non-conjugated NΛN ligands with strong ligand-field strength; 22, 25-28 the latter can be accomplished through attaching electron-donating groups to bpy, 29 or using electron-rich NΛN ligands, 30,31 such as 2-(1H-pyrazol-1-yl)pyridine (pzpy).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,19,20 However, high-energy emission is generally desired for many applications. [9][10][11] The former can be realized by including electron-withdrawing groups, such as F, to the phenyl ring of ppy, [21][22][23][24] or using non-conjugated NΛN ligands with strong ligand-field strength; 22, 25-28 the latter can be accomplished through attaching electron-donating groups to bpy, 29 or using electron-rich NΛN ligands, 30,31 such as 2-(1H-pyrazol-1-yl)pyridine (pzpy). [9][10][11] The former can be realized by including electron-withdrawing groups, such as F, to the phenyl ring of ppy, [21][22][23][24] or using non-conjugated NΛN ligands with strong ligand-field strength; 22, 25-28 the latter can be accomplished through attaching electron-donating groups to bpy, 29 or using electron-rich NΛN ligands, 30,31 such as 2-(1H-pyrazol-1-yl)pyridine (pzpy).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The former can be realized by including electron-withdrawing groups, such as F, to the phenyl ring of ppy, [21][22][23][24] or using non-conjugated NΛN ligands with strong ligand-field strength; 22, 25-28 the latter can be accomplished through attaching electron-donating groups to bpy, 29 or using electron-rich NΛN ligands, 30,31 such as 2-(1H-pyrazol-1-yl)pyridine (pzpy). [33][34][35] Such an approach seems more appealing than the commonly used F substitution, 24 as C-F bonds are reactive and tend to rupture upon excitation of the complex. [33][34][35] Such an approach seems more appealing than the commonly used F substitution, 24 as C-F bonds are reactive and tend to rupture upon excitation of the complex.…”
Section: Introductionmentioning
confidence: 99%
“…If at first sight, examination of such sophisticated complexes in devices can seem counter-intuitive, tris-heteroleptic complexes allow a high control of the emission wavelength without taking recourse to fluorination of the cyclometalated ligands. Indeed, since the pioneer works on iridium-based emitters, fluorination of the cyclometalated ligands has been extensively used and proved to be an effective tool to blue-shift the emission of complexes with a precision of 5e10 nm [50]. However, numerous works have recently evidenced the limitations of this strategy, defluorination of ligands occurring during complex synthesis [51e53] or during device operation [54,55].…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of LECs over OLEDs is their far simpler architecture and the fact that they can be assembled using solution processing. 25 Following studies of blue emitting complexes for OLEDs, 26,27 Evariste et al 28 demonstrated the use of cyclometallated methyland methoxy-substituted 2,3 0 -bipyridine ligands as the C^N domain in blue-emitting [Ir(C^N) 2 (4,4 0 -t Bu 2 bpy)] + complexes. In [Ir(C^N) 2 (N^N)] + complexes, the HOMO contains contributions from the Ir(III) dp orbitals and phenyl p-orbitals of the cyclometallated C^N ligands, and the LUMO is usually localized on the N^N ligand.…”
Section: Introductionmentioning
confidence: 99%